Familial Bell’s Palsy: A Case Report and Literature Review - Mark Kubik; Liliana Robles; Doris Kung (Case Reports in Neurological Medicine)
Objective. To describe a unique case of familial Bell’s palsy and summarize the current literature regarding possible hereditary influences. Design. Case report. Main Outcome Measures. Clinical exam, CSF analysis, and family history provided per the patient. Results. We report the case of a 58-year-old female who presented with recurrent and bilateral episodes of facial palsy. The patient underwent multiple CSF investigations to rule out a possible infectious and rheumatologic etiology that were all negative. Further questioning revealed she was one of seven family members with a history of unilateral facial nerve paralysis. Conclusion. The sheer number of similar case studies to date suggests that familial clustering of Bell’s palsy is a real, noncoincidental phenomenon. Our case represents a unique and perplexing example of one such family. Familial Bell’s palsy may represent an autoimmune disease secondary to inherited HLA alloantigens or a structural predisposition to disease based on the dimensions of the facial canal.